Silent resilience: an exploration of domestic, social and cultural spaces in informal settlements and their contribution in the limited access to education for disadvantaged women - Boora, Evelyn (My University, 2022)
Makause is a small informal community that has been affected by the deterioration of Primrose and Germiston. Unfortunately, the women of Makause have been disproportionately affected by this deterioration in the form of a face that looks like poverty. Their stories, their lives and their spaces have been defined and shaped by the de-industrialization of Germiston, and other people’s perceptions of them from the outside. They too have suffered inequality through spaces and policies that have been conceived by spatial planning in the urban landscape. They rely on informality, relationships and creating resilient strategies and networks to help them conquer and reimagine urban landscapes, proving that these women can be agents of change in the contested urban spaces if given the voice and the resources. Care, commoning and collective strategies can be further used in reclaiming the landscape through design strategies (Morrow & Parker, 2020). This research report explores how architecture can be used as a vehicle for social change, and create safe undiscriminating spaces for the women of Makause. Spaces where their resilience can solidify and become powerful devices for communal sustenance through empowerment and reclaiming the former mining landscape. It also explores how women and architecture can rewrite urban space using feminist lenses and perspectives. It also seeks to find ways of helping and teaching women techniques and skills related to farming and commercial production as Primrose plans to grow its commercialized district, it allows the intervention to be integrated into this plan without further marginalizing the women with gentrification. As mentioned before, Germiston was once a heavily industrialized area and the land in question was a former mining site. This research also seeks to interrogate the issues of land rehabilitation, metaphorically as a way of the community reclaiming the landscape and practically as a way of removing toxicity from communities living in former mining regions.
This research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Architecture (Professional)